Tinjauan Yuridis terhadap Perjanjian Kerja Yang Dibuat Secara Lisan - Fauzi Sumardi; Ridho Mubarak (Jurnal Ilmiah Penegakan Hukum, 2018)
Juridical Review Of Work Agreements Made OrallyA verbal work agreement is a work relationship that is made without the signing of a work agreement, a verbal work agreement is sufficient with a statement that is mutually agreed upon by both parties and should be witnessed by at least two witnesses. The purpose of this study was to find out how the legal strength of work agreements made verbally and how legal protection for workers whose employment relationships are based on verbal work agreements. The research method used is the library research method, namely by conducting research on various written reading sources, and the Field Research method, which is a juridical review of workers whose work relations are based on verbal work agreements. The purpose of this study is to find out the answers to the problems discussed. The results of the study indicate that the legal strength of the work agreement made orally is not specifically regulated in the Civil Code or in other laws and regulations so that the arrangement of oral agreements only follows the arrangement of work agreements in general